The value of U.S. beef exports and the traceability of pork in countries outside of North America - Meisinger, Jessica, author; Belk, Keith, advisor; Pendell, Dustin, committee member; Woerner, Dale, committee member; Engle, Terry, committee member (Colorado State University. Libraries, 2012)
Variation exists within beef cuts produced by U.S. beef packers for domestic and foreign markets, due to differences in consumer expectations and use of the product. The objective of this study was to conduct an industry-wide survey to identify commonality among and between U.S. beef processor specifications, as well as to identify differences between products sent to varying countries, and to determine a more accurate value of beef export. Countries that have an Export Verification program require suppliers to be certified with the United States Department of Agriculture and submit information about exported products. The EV information was collected and used to determine the countries that were receiving the highest volume of U.S. product, as well as the meat cuts common in each country. The data was also used to assign prices to individual products to ascertain export value. These documents do not show individual differences between how companies cut beef products. Four countries that represent significant U.S. beef export markets (Japan, Mexico, Hong Kong, and Taiwan) were visited. During these visits, product was visually checked and compared to known Institutional Meat Processor Specification (IMPS). Animal diseases and related food safety issues have become concerns to many people in the last decade and traceability is becoming increasingly important throughout the world as a way to control disease outbreaks before they have devastating effects on a country's livestock industries. The objective of this review was to discuss swine identification and traceability systems outside North America.
Keywords: traceability; pork; trade; beef; export